Meniscal lesions: from basic science to clinical management in footballers - Cengiz, I. F. (2017)
The knowledge related to meniscus biology, ultrastructure, and biomechanics has developed dramatically in the last years. Moreover, clinical data related to several different options for treatment has also increased. Nowadays, the tendency when dealing with meniscus tears is â preservation whenever possible.â Nevertheless, meniscectomy is still one of the most frequent orthopedic surgical procedures today. The development of repair techniques is making this option more and more possible and has been connected with surgical and technological improvements. The success rate of meniscus repair depends on several factors and is influenced by the location and type of tear. Moreover, any treatment option must consider patientâ s expectations. When dealing with high-level athletes (e.g., football), the player, the family, the manager, the club, and several other socioeconomic factors play a role, regardless of the surgeonâ s opinion. Classification of meniscal injuries, preoperative planning, and surgical training (including cadaver courses) are very important. Meniscus allograft transplantation and partial replacement by acellular scaffolds have been indicated in selected cases. However, there is few data supporting their use when return to high-level sports activity is the goal. This work aims to provide a comprehensive approach to the most frequent techniques and indications for treatment of meniscal injuries.